High Resolution Geothermal Heat Flux Data-Implications for Ice Sheet Dynamics and Model Uncertainty - Johnson, J.V; Näslund, Jens-Ove; Pattyn, Frank; Jansson, Peter (2007)
info:eu-repo/semantics/published